2004
DOI: 10.1158/0008-5472.can-03-3294
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxy-d-glucose Increases the Efficacy of Adriamycin and Paclitaxel in Human Osteosarcoma and Non-Small Cell Lung Cancers In Vivo

Abstract: Slow-growing cell populations located within solid tumors are difficult to target selectively because most cells in normal tissues also have low replication rates. However, a distinguishing feature between slow-growing normal and tumor cells is the hypoxic microenvironment of the latter, which makes them extraordinarily dependent on anaerobic glycolysis for survival. Previously, we have shown that hypoxic tumor cells exhibit increased sensitivity to inhibitors of glycolysis in three distinct in vitro models. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
322
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 419 publications
(339 citation statements)
references
References 19 publications
15
322
0
2
Order By: Relevance
“…Thus, addition of glycolytic inhibitors to current cancer therapies should increase their efficacies by preferentially targeting this hypoxic, slow-growing tumor cell population. In fact, 2-DG treatment was found to significantly enhance the ability of both Adriamycin and cisplatin to reduce the tumor volume of human osteosarcoma and non -small cell lung cancer cells growing in nude mice (7). These data correlate with a previous study in which it was shown that 2-DG in combination with an experimental anticancer agent dinaline showed increased antitumor efficacy (8).…”
Section: Introductionsupporting
confidence: 84%
“…Thus, addition of glycolytic inhibitors to current cancer therapies should increase their efficacies by preferentially targeting this hypoxic, slow-growing tumor cell population. In fact, 2-DG treatment was found to significantly enhance the ability of both Adriamycin and cisplatin to reduce the tumor volume of human osteosarcoma and non -small cell lung cancer cells growing in nude mice (7). These data correlate with a previous study in which it was shown that 2-DG in combination with an experimental anticancer agent dinaline showed increased antitumor efficacy (8).…”
Section: Introductionsupporting
confidence: 84%
“…As such, inhibitors of glycolysis including 3-bromopyruvate and 5-thioglucose provide promising therapeutic strategies (12,36). These inhibitors of glycolysis stand in contrast to 2DG, an inhibitor of glycolysis that has been advanced by other investigators as a potential therapeutic approach (25,37,38). Our results indicate a danger in using 2DG as an anticancer therapy because treatment with 2DG in the setting of glucose withdrawal prevented rather than promoted cell death.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, several glycolytic inhibitors that target key glycolytic enzymes have been tested for their anticancer activity in vitro and in vivo. [4][5][6][7][8] Such a metabolic intervention seems to produce encouraging results, at least in experimental model systems.…”
Section: Introductionmentioning
confidence: 99%